Women in the Reformation Era - Pangestu, Ahmad Dimas Jihan; Mahfud (CV. Sekawan Siji, 2024)
This article discusses the role of women in the context of social, political, and economic changes during the reform era in Indonesia. The reform era, which began in 1998, marked a significant transition in the political and social life of Indonesia, introducing democratization, decentralization, and civil freedoms. In this framework, Indonesian women faced new challenges and opportunities in various sectors, including politics, education, economy, and culture. Although gender gaps still exist, women have gained greater access to strategic positions and have played an active role in policymaking. This article analyzes the development of women's rights, the challenges they face, and their contributions to strengthening Indonesia's democratic system post-reform.